Qualidade fisiológica das mudas na produção de frutas do morangueiro - Cocco, Carine (2010)
The objective of this research was to determine plant growth and development and fruit yield of the strawberry crop from bare root and plug transplants with different crown diameters. Bare roots transplants were produced by rooting stolons and plug transplants from runner tips collected and rooted in a substrate growing bed. Three classes of crown diameters were compared, in a 2 x 3 factorial and randomized block experimental design, with four replications, 16 plants per plot and a density of 6.6 plants m-2. For bare root transplants, crown diameters were between 3.0 and 5.0 (class 1); 5.1 and 8.0 (class 2) and greater than 8.1 mm (class 3). For plug transplants, runner tips were screened between 2.0 and 3.9 (class 1); 4.0 and 5.5 (class 2) and 5.6 to 7.0 mm (class 3). Transplants of both types were planted at April 16th, 2008, and at this date, crown diameter, shoot and root dry mass and number of leaves were higher in all classes of plug transplants. Ripe fruits were harvested from June 15th to November 7th, 2008, and fresh fruit yield was determined. Plant growth and development were determined at last harvest. Higher growth, development and fruit yield were obtained in plants from plug transplants. For bare root transplants, crown diameters higher than 5.1 mm can be used while for plug transplants the crown diameter of runner tips does not affect plant growth and fruit yield.